2018
DOI: 10.1093/infdis/jiy033
|View full text |Cite
|
Sign up to set email alerts
|

Novel Function of Cyclooxygenase-2: Suppressing Mycobacteria by Promoting Autophagy via the Protein Kinase B/Mammalian Target of Rapamycin Pathway

Abstract: In Mycobacterium tuberculosis-infected macrophages, cyclooxygenase-2 (COX-2) expression considerably increases to defend the body against mycobacteria by regulating adaptive immunity and restoring the mitochondrial inner membrane. Moreover, in cancer cells, COX-2 enhances the autophagy machinery, an important bactericidal mechanism. However, the association between M. tuberculosis-induced COX-2 and autophagy-mediated antimycobacterial response has not been explored. Here, COX-2 expression silencing reduced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 45 publications
2
24
0
2
Order By: Relevance
“…These observations demonstrated that COX-2 participates in the regulation of autophagy induced by WNT5A following M. tuberculosis infection. It has recently been reported that activation of autophagy by COX-2 in macrophages is through AKT/mTOR signaling to suppress mycobacterial survival in bone marrow-derived macrophages (36). Consistently, a decrease in activation of AKT and mTOR was observed in MDMs exposed to rhWNT5A, whereas small interfering WNT5A (si-WNT5A) upregulated their levels (Fig.…”
Section: Il-36g Mediated the Bactericidal Activity Partly Through Thesupporting
confidence: 72%
“…These observations demonstrated that COX-2 participates in the regulation of autophagy induced by WNT5A following M. tuberculosis infection. It has recently been reported that activation of autophagy by COX-2 in macrophages is through AKT/mTOR signaling to suppress mycobacterial survival in bone marrow-derived macrophages (36). Consistently, a decrease in activation of AKT and mTOR was observed in MDMs exposed to rhWNT5A, whereas small interfering WNT5A (si-WNT5A) upregulated their levels (Fig.…”
Section: Il-36g Mediated the Bactericidal Activity Partly Through Thesupporting
confidence: 72%
“…In this regard, it has been shown that cyclic mechanical stretching induces autophagic cell death in tenofibroblasts through the activation of PGE2production 11 and that nicotine induces cell stress and autophagy mediated by COX-2 activation and PGE2 production in human colon cancer cells 12 . Furthermore, it was recently described that the expression of COX-2 contributes to increase autophagy and therefore to eliminate Mtb in bone marrow murine derived macrophages 13 . Nevertheless, this modulation has not been described yet in primary human cells.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, kidney autophagy levels were shown to decrease after silencing PGES-2 33 . Importantly, Xiong et al reported that COX-2 suppresses mycobacterial growth in murine macrophages by promoting autophagy via the AKT/mTOR pathway 13 . Strikingly, other authors described that the PGE2 reverses vitamin D3-induced autophagy in macrophages infected with Mtb 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is an efficient cellular process for the host to eliminate pathogens, and COX-2 was reported to be beneficial for the clearance of M. tuberculosis by promoting autophagy (Xiong et al, 2018). To explore the effect of COX-2 inhibition on autophagy in ExPEC-infected macrophages, the expression level of the autophagy formation marker LC3, which is converted into LC3-II from LC3-I, was assessed in the study.…”
Section: Cox-2 Inhibition Attenuated Macrophage Autophagy During Expementioning
confidence: 99%
“…COX-2 mediated PG production was also demonstrated to be involved in inducing autophagy in various physiological processes (Kar et al, 2009;Choi et al, 2014;Pelissier-Rota et al, 2015). However, the function of autophagy in ExPEC infection may vary depending on the strain and pathotype, and the association between ExPEC-induced COX-2 expression and autophagy formation has not yet been elucidated (Xiong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%